Artifact‐free objective‐type multicolor total internal reflection fluorescence microscopy with light‐emitting diode light sources—Part I. Issue 11 (23rd July 2019) - Kogel, Alexander; Kalwa, Hermann; Urban, Nicole; Schaefer, Michael
Abstract: Total internal reflection fluorescence excitation (TIRF) microscopy allows the selective observation of fluorescent molecules in immediate proximity to an interface between different refractive indices. Objective‐type or prism‐less TIRF excitation is typically achieved with laser light sources. We here propose a simple, yet optically advantageous light‐emitting diode (LED)‐based implementation of objective‐type TIRF (LED‐TIRF). The proposed LED‐TIRF condenser is affordable and easy to set up at any epifluorescence microscope to perform multicolor TIRF and/or combined TIRF‐epifluorescence imaging with even illumination of the entire field of view. Electrical control of LED light sources replaces mechanical shutters or optical modulators. LED‐TIRF microscopy eliminates safety burdens that are associated with laser sources, offers favorable instrument lifetime and stability without active cooling. The non‐coherent light source and the type of projection eliminate interference fringing and local scattering artifacts that are associated with conventional laser‐TIRF. Unlike azimuthal spinning laser‐TIRF, LED‐TIRF does not require synchronization between beam rotation and the camera and can be monitored with either global or rolling shutter cameras. Typical implementations, such as live cell multicolor imaging in TIRF and epifluorescence of imaging of short‐lived, localized translocation events of a Ca 2+ ‐sensitive protein kinase C α fusion protein are demonstrated. Abstract : Processes and objects close to the plasma membrane are key contributors to cell communication and function that can be selectively imaged by total internal reflection fluorescence (TIRF) microscopy. As an affordable yet effective alternative of laser‐TIRF setups, we propose a simple light‐emitting diode (LED)‐based beampath. The spatial and temporal resolution capabilities of LED‐TIRF are demonstrated, applying a set of typical cell biological imaging tasks.